Effect of thermal conditioning on growth performance and thermotolerance in broilers: A systematic review and meta-analysis. (May 2021) - Ncho, Chris Major; Gupta, Vaishali; Goel, Akshat
Abstract: Thermal conditioning has been introduced as a cost-effective way to improve performance and thermotolerance in broilers. However, since all the trials were performed under various experimental conditions, it appears difficult to draw general conclusions. Therefore, the objective of this study was to quantify the response of broilers to thermal conditioning through a meta-analysis approach. A literature search was conducted on Scopus, PubMed, Scielo, Web of Science, and Google scholar in December 2020. A restricted maximum likelihood random effect model was used to pool the effect sizes from the body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), and body temperature (Tb). BWG, FI, and Tb were computed using the standardized mean difference (SMD) while FCR was computed using mean differences (MD) with a 95% confidence interval (IC). Growth performances were evaluated during the thermoneutral conditions while Tb was evaluated after either acute or chronic heat stress after early age thermal conditioning. A total of 17 studies were included in the dataset. Thermal conditioning significantly increased BWG (SMD = 0.139, IC = 0.0372–0.2407, P = 0.0074) and FI (SMD = 0.292, IC = 0.108–0.476, P = 0.0019) compared with the control. Additionally, subgroup analysis revealed that overall Tb was significantly reduced under acute heat stress (SMD = -0.455, IC = -0.718 to −0.192, P < 0.001) but not affected during chronic heat stress (SMD = -0.115, IC = -0.651 to −0.420, P = 0.6729). In conclusion, thermal conditioning significantly increased the broiler's BWG and FI under thermoneutral conditions and can help in reducing Tb under acute heat stress. Highlights: Thermal conditioning improves growth performances of broiler in terms of the body weight gain and feed intake under thermoneutral temperature conditions. Early age thermal conditioning effectively reduces the broiler's body temperature under acute heat stress. No variation was observed in the body temperature of chronic heat stress birds when chicks were exposed to early age thermal conditioning.